2020
DOI: 10.6023/cjoc201907033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Novel Spiro[chromo(2,3-c)-pyrazole-4,1'-isobenzofuran]-3'-one Compounds

Abstract: Synthesis and Optical Properties of Novel Spiro[chromo(2,3-c)pyrazole-4,1'-isobenzofuran]-3'-one Compounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…to 2 equiv., the hydrogen on the secondary amines (À NHÀ ) at 11.51 ppm weaken gradually, but did not disappear, and the hydrogen on other positions had almost no change (Figure 8b, c, d). Based on the above experimental results and the literatures [40][41][42][43], the plausible mechanism of BS-Hg 2 + is proposed (Figure 9). And this experiment results could be verified by mass spectrometry (m/z 734.0939 [BS + Hg 2 + + Na + ] + ) (Figure S12).…”
Section: H Nmr Titration Experimentsmentioning
confidence: 64%
See 2 more Smart Citations
“…to 2 equiv., the hydrogen on the secondary amines (À NHÀ ) at 11.51 ppm weaken gradually, but did not disappear, and the hydrogen on other positions had almost no change (Figure 8b, c, d). Based on the above experimental results and the literatures [40][41][42][43], the plausible mechanism of BS-Hg 2 + is proposed (Figure 9). And this experiment results could be verified by mass spectrometry (m/z 734.0939 [BS + Hg 2 + + Na + ] + ) (Figure S12).…”
Section: H Nmr Titration Experimentsmentioning
confidence: 64%
“…And the linear regression equation was y = À 22.88x + 865.6 (R 2 = 0.9982). Based on the 3σ/k, [40][41][42][43][44] the lowest detection limit (LOD) of BS for Hg 2 + was found to be 2.84 × 10 À 8 M. Excellent linear correlation and low detection limit indicated that BS could not only qualitatively detect Hg 2 + , but also quantitatively detect Hg 2 + in a certain concentration range.…”
Section: Sensitivity Experiments Of Bs Towards Hg 2 +mentioning
confidence: 99%
See 1 more Smart Citation
“…Schiff bases contain C=N bands that show strong binding affinities for metal ions and the synthesis steps are relatively simple. Based on this research and combined with the previous work of our team, [ 27–41 ] we designed and synthesized a novel benzenesulfonyl hydrazone, the highly efficient fluorescent probe DBTBH , using the condensation reaction of aldehydes and benzenesulfonyl hydrazide for the selective and sensitive detection of Pb 2+ in highly aqueous media and without any interference from other metal cations and anions. As far as we know, this is the first time that the structure of benzenesulfonyl hydrazone has been reported as a fluorescent probe.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, based on previous work of our laboratory, a novel sulfonyl hydrazone probe S1 was synthesized by simple condensation of benzene sulfonyl hydrazine with 4-diphenylamino benzaldehyde (Scheme 1). [34][35][36][53][54][55][56][57][58][59][60][61][62][63][64] As compared to other probes reported before, sulfonyhydrazone based probes S1 displayed superiority from the viewpoint of high selectivity, sensitivity and ease in detection. Moreover, this probe can be applied for the detection of Hg 2+ in HeLa cells, which shows good biocompatibility and can evidently enhance the fluorescence in live cells imaging.…”
Section: Introductionmentioning
confidence: 99%